Trans-Tasman Liaison: Australasian Defence Co-ordination and the New Zealand Military Liaison Offices in Australia, 1932–48. Issue 2 (4th March 2022) - Leach, Daniel
ABSTRACT: This article examines attempts at defence policy co-ordination between Australia and New Zealand before, during and immediately after the Second World War, with emphasis upon the establishment, role and significance of the New Zealand Liaison Offices (NZLOs) in Australia across their most active lifespan of 1940–1948. Employing official correspondence housed in the national archives of both countries, it argues that, although the NZLOs facilitated close wartime co-operation between the two Imperial partners in areas such as munitions supply, this did not necessarily translate into closer co-ordination in defence policy. In time the war presented opportunities for the establishment of direct defence ties no longer relayed through London, yet these too largely failed to live up to their promise. Ranging from pre-war visits by NZ general staff to the significant downgrading of the NZLO in Sydney in 1948, this article places the NZLOs in their proper historical context, establishing them and trans-Tasman military relations as an intrinsic yet often overlooked part of both the Australian and New Zealand wartime experience.